Prevalence and Predictors of Internet Addiction among College Students in Sousse, Tunisia - Mellouli, Menel (J Res Health Sci, 2017)
Background: Internet represents a revolution in the world of technology and communication all over the world including Tunisia. However, this technology has also introduced problematic use, especially among students. The current study aimed to determine the prevalence of Internet addiction among college students and its predictors in the region of Sousse, Tunisia. Study design: A cross-sectional study. Methods: The current study was conducted in the colleges of Sousse, Tunisia in 2012-2013. A self-administrated questionnaire was used to collect data from 556 students in 5 randomly selected colleges from the region. Collected data concerned socio-demographic characteristics, substances use and internet addiction using the Young Internet Addiction Test. Results: The response rate was 96%. The mean age of participants was 21.8 ±2.2 yr. Females represented 51.8% of them. Poor control of internet use was found among 280 (54.0%; 95% CI: 49.7%, 58.3%) participants. Low education levels among parents, the young age, lifetime tobacco use and lifetime illicit drugs use were significantly associated with poor control of internet use among students (P<0.001). While, the most influential factor on internet use among them was under-graduation with an adjusted odds ratio of 2.4 (95% CI: 1.7, 3.6). Conclusions: Poor control of internet use is highly prevalent among the college students of Sousse especially those under graduate. A national intervention program is required to reduce this problem among youth. A national study among both in-school and out-of-school adolescents and young people would identify at-risk groups and determine the most efficient time to intervene and prevent internet addiction.